2017
DOI: 10.4269/ajtmh.17-0221
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Serotypes 1 and 2 Responsible for Major Dengue Outbreaks in Nepal: Clinical, Laboratory, and Epidemiological Features

Abstract: Abstract.Dengue virus (DENV) is expanding toward previously nonendemic areas. DENV has recently been introduced in Nepal with limited information. We report the clinical features and serotype distribution of DENV in Nepal during the 2010 outbreaks. A total of 1,215 clinical dengue cases at two major hospitals of central and western Nepal were investigated. Demographic, clinical, and laboratory parameters were recorded. Serum specimens were tested for DENV by IgM/IgG enzyme-linked immunosorbent assays (ELISAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 35 publications
3
43
0
1
Order By: Relevance
“…On analysis of seasonal variability, we found the number of dengue patients peaked in October and November. Similar variation was observed in other studies conducted in Nepal 11,16 , but studies conducted in China, India, Pakistan and Bangladesh found August and October to be peaked season for dengue. 5,6,11,[17][18][19]21 These observations might indicate that seasonal outbreaks in these countries are closely related and there might be consistent transmission of the disease among these countries.…”
Section: Table1: Clinical Features Of Patients Presented With In Dengsupporting
confidence: 88%
See 3 more Smart Citations
“…On analysis of seasonal variability, we found the number of dengue patients peaked in October and November. Similar variation was observed in other studies conducted in Nepal 11,16 , but studies conducted in China, India, Pakistan and Bangladesh found August and October to be peaked season for dengue. 5,6,11,[17][18][19]21 These observations might indicate that seasonal outbreaks in these countries are closely related and there might be consistent transmission of the disease among these countries.…”
Section: Table1: Clinical Features Of Patients Presented With In Dengsupporting
confidence: 88%
“…These symptoms were also predominant in studies from Nepal 22 , India 17,18 Pakistan6, and Taiwan. 23 However another study conducted in Nepal 16 and in Pakistan, 19 fever with headache and nausea vomiting were the most predominant features. In addition to that, cough and anorexia were also the observed symptoms in our study which were also observed in other studies conducted in India and Pakistan.…”
Section: Table1: Clinical Features Of Patients Presented With In Dengmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, we cannot overlook the serologically positive cases reported in 2004 and 2007 in Kathmandu valley [8,9] In Nepal, scrub typhus cases were reported nationwide (52 of 75 districts) in just three years since the disease may expand very rapidly as seen in other parts of the world [29,30]. In this study, the majority of cases were reported from lowland terai districts where other febrile illnesses including Japanese encephalitis (JE) [31,32], leptospirosis [33], and dengue [31,32] had been frequently reported. Even before the initiation of JE vaccination in Nepal, only onethird of the acute encephalitis syndrome (AES) cases were due to JE, which declined with immunization, however the AES still remains persistent clearly indicating other aetiologies of AES in the country.…”
Section: Discussionmentioning
confidence: 72%